PENGARUH PROMOSI PENJUALAN TERHADAP KEPUTUSAN PEMBELIAN MEBEL PADA CV. LAUTAN REZEKI PEKANBARU - Fakhri, Rizqi (Sekolah Tinggi Ilmu Ekonomi Riau, 2020)
This study aims to Know Sales Promotion Effect onÂ Purchase Decision Furniture at CV. Lautan Rezeki Pekanbaru. The sample in this study amounted to 51 store, while the sampling technique using Accidental Sampling method. The data analysis in this study with descriptive and quantitative methods with simple linear regression. Based on the research results through tests T, the value is greater thitung 7,002 dati t table with ttable value of 2,009, with a significance level of 0.000 < 0.05. Thus, it means sales promotion variable (X) significantly influence the purchase decision variable (Y). It can be concluded that promotional sales significantly influence buying decisions Furniture on the CV. Lautan Rezeki Pekanbaru. Based on the result of determination, so in this study can be concluded that the sales promotion variable effect of 50% on purchasing decisions furniture in the CV. Lautan Rezeki Pekanbaru. while the remaining 50% is influenced by other variables that are ignored or are not examined in this study